2020
DOI: 10.1109/lcomm.2020.3006554
|View full text |Cite
|
Sign up to set email alerts
|

Performance Limits of Fluid Antenna Systems

Abstract: Fluid antenna represents a concept where a positionflexible antenna can switch its location freely within a given space. Recently, it has been demonstrated that even with a tiny space, a single-antenna fluid antenna system (FAS) can outperform an L-antenna maximum ratio combining (MRC) system in terms of outage probability if the number of locations (or ports) the fluid antenna can be switched to, is large enough. This letter aims to study if extraordinary capacity can also be achieved by FAS with a small spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…This paper uses the term 'fluid antenna' to represent a reconfigurable system that can automatically switch the antenna position to the best of N fixed locations (referred to as 'ports') within a given space instantly. The diversity benefit of fluid antenna for single-user communication was analyzed in terms of outage probability in [36] while [37] has already examined the ergodic capacity of a single-user fluid antenna system. It was revealed that with a space of half a wavelength or less, a single fluid antenna system with only one RF chain can obtain as much capacity as a maximum ratio combining system with many spatially uncorrelated antennas.…”
Section: Introductionmentioning
confidence: 99%
“…This paper uses the term 'fluid antenna' to represent a reconfigurable system that can automatically switch the antenna position to the best of N fixed locations (referred to as 'ports') within a given space instantly. The diversity benefit of fluid antenna for single-user communication was analyzed in terms of outage probability in [36] while [37] has already examined the ergodic capacity of a single-user fluid antenna system. It was revealed that with a space of half a wavelength or less, a single fluid antenna system with only one RF chain can obtain as much capacity as a maximum ratio combining system with many spatially uncorrelated antennas.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid switch improves the isolation of the two bands and avoids biasing line disturbances. More recently, the authors of [72] and [73] proposed a new fluid antenna system (FAS) where a position-flexible antenna can switch its location freely within a given space. It was demonstrated that even with a tiny space, a single-antenna FAS can outperform a multiple-antenna maximum ratio combining system in terms of outage probability if the number of locations (or ports) the fluid antenna can be switched to is large enough.…”
Section: B Pure Water Antennasmentioning
confidence: 99%
“…1 illustrates the concept of a possible realisation on a handset where conductive fluid is installed on a tube‐like structure within which the fluid is free to move. In this design example, the shape of the antenna cannot be changed but its position can, which may be exploited for diversity and capacity benefits [6 ].…”
Section: What Is Fluid Antenna?mentioning
confidence: 99%
“…Fluid antenna research is still at an early stage, although the ideas of using liquid based antennas have been researched for over a decade, and the performance limits under idealised conditions have also recently been studied in [6 ],[14 ],[15 ]. There are major obstacles that still need to be overcome satisfactorily, should fluid antenna play a key role in 6G.…”
Section: Challengesmentioning
confidence: 99%